PEDAGOGY OF PARTNERSHIP AS A FACTOR OF FORMATION OF EFFECTIVE INTERACTION OF PARTICIPANTS OF THE EDUCATIONAL PROCESS IN THE CONDITIONS OF THE NEW UKRAINIAN SCHOOL - Fedirchуk Tatiana; Didukh Vitaliіа (Mountain School of Ukrainian Carpaty, 2019)
The article describes the essence of the concept of «partnership pedagogy», outlines the principles and principles on which partnership pedagogy is based on the Concept of the New Ukrainian School, and proves the necessity to study this line of pedagogy. Partnership pedagogy is substantiated as a component of the formation of the innovative educational space of the New Ukrainian School from a psychological and pedagogical standpoint. The results of the study of the level of willingness of future primary school teachers to interact with the participants of the educational process on the basis of partnership pedagogy are presented. During the reforms and changes in the Ukrainian education, especially in elementary school, to optimize the learning process should take a look you on the interaction between the participants of the educational process in the light of new approaches that include: creating a favorable atmosphere of cooperation and collaboration; the transition from the practice of transferring teacher material that can be obtained from available sources and transition to active communication with students during educational activities; intensification of the introduction into the educational process of "active" teaching methods that are aimed at disclosing the individual, developing his initiative, motivation for cognitive activity, which is disclosed in the current normative documents of the education system, namely in the Law of Ukraine "On Education" and in the Concept "New Ukrainian School". The analysis of the def and nition of the concept of "partnership" testifies to its multidimensionality. Partnership pedagogy is considered by scientists as a well-defined system of relationships between all participants in the educational process (students, educators, managers , parents), which is based on the principle of voluntariness , which is based on the respect and equality of all participants, while respecting certain norms (rights and obligations ) the benchmarks of each party; involves the active involvement of all participants in the implementation of common tasks and the willingness to take responsibility for their results. Thus, pedagogy of partnership acts as a factor of effective interaction of participants in the educational process in the New Ukrainian School , whose main purpose is to support students, which contributes to the development of their abilities, satisfies the intellectual, emotional and social needs of children, which meets the needs of modern educational theory .